2005
DOI: 10.1021/jo051525i
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric Total Synthesis of Dibenzocyclooctadiene Lignan Natural Products

Abstract: [structure: see text] Full details of the asymmetric total syntheses of the dibenzocyclooctadiene lignans interiotherin A, angeloylgomisin R, gomisin O, and gomisin E (epigomisin O) are presented. The syntheses were based on a unified synthetic strategy involving a novel crotylation using the Leighton auxiliary that occurred with excellent asymmetric induction (>98:2 enantiomeric ratio), a diastereoselective hydroboration/Suzuki-Miyaura coupling reaction sequence, and an atropdiastereoselective biarylcuprate c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 92 publications
0
22
0
1
Order By: Relevance
“…Intramolecular couplings were used in synthesis of isocomplestatin [244] and biphenomycin B [245]. (11) Alkyl boron reagents were used in synthesis of for example minfiensine [246], zoapatanol [247], dibenzocyclooctadiene lignans [248,249], the C1-C25 fragment of amphidinol 3 [250], (+)-SCH-351448 [251], the C10-C24 fragment of inostamycins [252], (+)-brefeldin C [253], (+)-wortmannin [254], cordiaquinone J and K [255] and cannabinoid antagonists [256].…”
Section: Carbon-carbon Bond-forming Reactions Via Transmetallationmentioning
confidence: 99%
See 2 more Smart Citations
“…Intramolecular couplings were used in synthesis of isocomplestatin [244] and biphenomycin B [245]. (11) Alkyl boron reagents were used in synthesis of for example minfiensine [246], zoapatanol [247], dibenzocyclooctadiene lignans [248,249], the C1-C25 fragment of amphidinol 3 [250], (+)-SCH-351448 [251], the C10-C24 fragment of inostamycins [252], (+)-brefeldin C [253], (+)-wortmannin [254], cordiaquinone J and K [255] and cannabinoid antagonists [256].…”
Section: Carbon-carbon Bond-forming Reactions Via Transmetallationmentioning
confidence: 99%
“…Copper mediated an intramolecular coupling of two aryl bromides in a synthesis of dibenzocyclooctadiene lignans (Eq. (26)) [249,250].…”
Section: Carbon-carbon Bond-forming Reactions Using Terminal Alkynes mentioning
confidence: 99%
See 1 more Smart Citation
“…To form the axially chiral biaryl system, various strategies have been devised. [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24] Homocoupling of aryl halides bearing a chiral oxazoline moiety by the Ullmann reaction has been used to synthesize unsymmetrical biaryls. [25][26][27][28] One of the two diastereomers of a C 2 -symmetrical chiral bisoxazoline may be obtained by the combination between the ligand and a metal ion.…”
Section: Introductionmentioning
confidence: 99%
“…However, because natural lignans with multiple chiral centers are not always ideal as drug candidates, even though many total synthesis studies have been reported,13 we were prompted to use lignans as leads for new compounds with simpler, more accessible structures. The biphenyl moiety in natural dibenzocyclooctadiene lignans is substituted with methoxy and methylenedioxy groups at different positions, resulting in either symmetrical (wuweizi C) or unsymmetrical (wuweizi B) biphenyls, as shown in Figure 1, and this feature is crucial for biological activity.…”
mentioning
confidence: 99%